Phytochrome B Negatively Affects Cold Tolerance by Regulating OsDREB1 Gene Expression through Phytochrome Interacting Factor-Like Protein OsPIL16 in Rice - He, Yanan; Li, Yaping; Cui, Lixin; Xie, Lixia; Zheng, Chongke; Zhou, Guanhua; Zhou, Jinjun; Xie, Xianzhi (Frontiers in Plant Science, 2016)
Cross talk between light signaling and cold signaling has been elucidated in the model plant Arabidopsis and tomato, but little is known about their relationship in rice. Here, we report that phytochrome B (phyB) mutants exhibit improved cold tolerance compared with wild type (WT) rice (Oryza sativa L. cv. Nipponbare). The phyB mutants had a lower electrolyte leakage index and malondialdehyde concentration than the WT, suggesting that they had greater cell membrane integrity and less lipid peroxidation. Real-time PCR analysis revealed that the expression levels of dehydration-responsive element binding protein 1 (OsDREB1) family genes, which functions in the cold stress response in rice, were increased in the phyB mutant under normal and cold stress conditions. PIFs are central players in phytochrome-mediated light signaling networks. To explore the relationship between rice PIFs and OsDREB1 gene expression, we produced overexpression lines of rice PIF genes. OsDREB1 family genes were up-regulated in OsPIL16-overexpression lines, which had improved cold tolerance relative to the WT. Chromatin immunoprecipitation (ChIP)-qPCR assay revealed that OsPIL16 can bind to the N-box region of OsDREB1B promoter. Expression pattern analyses revealed that OsPIL16 transcripts were induced by cold stress and was significantly higher in the phyB mutant than in the WT. Moreover, yeast two-hybrid assay showed that OsPIL16 can bind to rice PHYB. Based on these results, we propose that phyB deficiency positively regulates OsDREB1 expression through OsPIL16 to enhance cell membrane integrity and to reduce the malondialdehyde concentration, resulting in the improved cold tolerance of the phyB mutants.